Impact of Lapsed Policies in Life Insurance Industries of Nepal - Koju, Ram; Subedi, Susil Dev; Koju, Laxmi (Nepalese Journal of Insurance and Social Security, 2020)
Growth and competition are rapidly rising in life insurance sector. Companies have challenge to stay in the market and earn profit as well as build trust among the end users. In this context, companies have to expand business by selling more life insurance policies. However, only selling new policies might not be the solution to increase profit. Thus, company needs to ensure minimum to zero lapse rates for the sustainable growth of the company. This study investigated the impact of lapse rate and revival rate on net worth, profitability, life fund, and total premium income of life insurance industries in Nepal over the period 2010-2019. The study employed Generalized Method of Moments (GMM) for empirical estimation. The empirical results showed the lapse rate, profitability, revival rate and surrender rate of 23.91%, 2.64%, 88.82% and 3.83%, respectively in the life insurance industries in Nepal during the 10 years’ period. The lapse rate was significantly negatively correlated with life fund and the total premium income with the–model coefficients of 0.1474065 and -0.19244, respectively. Moreover, the empirical estimation showed a significant positive correlation between lapse rate and profitability. This might be because high lapse rate lowers the provision of unexpired risk and life fund resulting in higher amount of profitability. The revival rate was significantly positively correlated with the profitability. This might be because higher revival rate increases the renewal income of a company, resulting in more funds available for investment thereby bringing positive cash inflow for the company. However, the revival rate did not show any significant association with net worth, life fund and total premium income.